Monoclonal antibodies in the treatment of multiple sclerosis: emergence of B‐cell‐targeted therapies. (26th April 2017) - Nguyen, Ai‐Lan; Gresle, Melissa; Marshall, Tessa; Butzkueven, Helmut; Field, Judith
Abstract: Multiple sclerosis (MS) is a chronic inflammatory disease of the CNS, and one of the most common causes of disability in young adults. Over the last decade, new disease‐modifying therapies have emerged, including monoclonal antibodies (mAbs) that provide highly targeted therapies with greater efficacy than platform therapies. In particular, monoclonal antibodies directed against CD20‐positive B cells have shown remarkable results in recent clinical trials and renewed interest in the mechanism of B cell‐depleting therapies to ameliorate relapse activity and progression in MS. Here, we review the mechanisms of action and clinical evidence of approved and emerging mAbs, with a focus on B cell‐targeted therapies.